Temperature variation of reaction liquid of ultrafine corn stover in photosynthetic hydrogen production - Quanguo, Zhang; Yingkuan, Wang; Jianjun, Hu; Jie, Guo; Zhiping, Zhang; Yanyan, Jing; Guangyin, Xu; Yi, Wang (International Journal of Agricultural and Biological Engineering, 2014)
The thermo-physical phenomena existing in the process of hydrogen production by photosynthetic bacteria with ultrafine corn stover directly affect the energy consumption of biological hydrogen production system, the activity of hydrogen production, and hydrogen production rate. In order to discover theoretical basis for optimizing process parameters of the photosynthetic bioreactor for ultrafine corn stover, experimental investigation was conducted to identify the effects of the granularity of ultrafine corn stover on the temperature variation using a self-developed photosynthetic bio-hydrogen thermal-effect experimental device. This paper describes experimental research on temperature variation of reaction liquid with ultrafine-ground corn stover in photosynthetic hydrogen production, and on the temperature field and change trend of reaction liquid of corn stover with different granularities in bio-hydrogen production. Experimental results showed that, the greater the granularity of corn stover, the slower the temperature rising speed of the reaction liquid with corn stover in the initial phase of photosynthetic hydrogen production, and the lower the relative average temperature of reaction liquid in photosynthetic hydrogen production. This result is of great significance in research on the photosynthetic hydrogen production technology from biomass, providing a theoretical basis for thermal effect in solar photosynthetic hydrogen production. Keywords: corn stover, photosynthetic hydrogen production, ultrafine grinding, bioreactor, granularity, temperature DOI: 10.3965/j.ijabe.20140705.009 Citation: Zhang Q G, Wang Y K, Hu J J, Guo J, Zhang Z P, Jing Y Y, Xu G Y, Wang Y. Temperature variation of reaction liquid of ultrafine corn stover in photosynthetic hydrogen production. Int J Agric & Biol Eng, 2014; 7(5): 65－71.